Effect of tanshinone IIA for myocardial ischemia/reperfusion injury in animal model: preclinical evidence and possible mechanisms - Zhu, Peng-Chong; Shen, Jiayi; Qian, Ren-Yi; Xu, Jian; Liu, Chong; Hu, Wu-Ming; Zhang, Ying; Lv, Ling-Chun (Frontiers in Pharmacology, 2023)
Tanshinone IIA (Tan IIA), the major active lipophilic ingredient of Radix Salviae Miltiorrhizae, exerts various therapeutic effects on the cardiovascular system. We aimed to identify the preclinical evidence and possible mechanisms of Tan IIA as a cardioprotective agent in the treatment of myocardial ischemia/reperfusion injury. The study quality scores of twenty-eight eligible studies and data analyses were separately assessed using the CAMARADES 10-item checklist and Rev-Man 5.3 software. The study quality score ranged from 3/10 to 7/10 points. The present study provided preliminary preclinical evidence that Tan IIA could significantly decrease the myocardial infarct size, cardiac enzyme activity and troponin levels compared with those in the control group (P < 0.05). Tan IIA alleviated myocardial I/R injury via antioxidant, anti-inflammatory, anti-apoptosis mechanisms and improved circulation and energy metabolism. Thus, Tan IIA is a promising cardioprotective agent for the treatment of myocardial ischemia/reperfusion injury and should be further investigated in clinical trials.